Environmental Protection and BITs of Bangladesh, Malaysia and USA: A Comparison - Hossain, Mohammad Belayet (Jurnal Cita Hukum, 2020)
Abstract In absence of any global treaty, the bilateral investment treaties (BITs) are playing an important role in regulating foreign investments in the host countries. According to the United Nations Conference on Trade and Development, there are 2361 BITs in force and like other members of the World Trade Organization, Bangladesh, Malaysia, and the USA also signed BITs to facilitate trade. The primary purpose of economic globalization is the economic development of the developing and least-developed countries as well as to facilitate the benefits of the home states. Bangladesh and Malaysia foreign investment laws have no specific provision of protecting the environment and fails to maintain high standard like USA environment laws. This paper addresses two questions: (a) do the bilateral investment treaties of Bangladesh, Malaysia, and USA have any specific provisions to protect the environment in the host country? (b) should environmental protection be considered during the entry of foreign investments in Bangladesh, Malaysia, and USA? Using the doctrinal research method, we critically analyzed 40 BITs signed by Bangladesh, Malaysia, and USA with different countries to explore whether there is any specific reference to protecting the environment. We find that the existing BITs mainly have provisions to promote and protect foreign investments, and 7 out of 40 BITs have a specific reference to protecting the environment. Therefore, governments should consider this important factor to insert while signing any future BITs.Keywords: Bilateral investment treaties, environmental protection, Bangladesh, Malaysia, United States of America. AbstrakJika tidak ada perjanjian global, maka perjanjian investasi bilateral (BIT) memainkan peran penting dalam mengatur investasi asing di negara setempat. Menurut Konferensi Perserikatan Bangsa-Bangsa tentang Perdagangan dan Pembangunan, ada 2.361 BIT yang masih berlaku, dan seperti anggota Organisasi Perdagangan Dunia lainnya, maka negara Bangladesh, Malaysia, dan AS juga menandatangani BIT untuk memfasilitasi perdagangan. Tujuan utama globalisasi ekonomi adalah pembangunan ekonomi negara-negara berkembang dan negara tidak berkembang, serta untuk memfasilitasi keuntungan negara asal. Undang-undang investasi asing Bangladesh dan Malaysia tidak memiliki ketentuan khusus untuk melindungi lingkungan dan gagal mempertahankan standar tinggi seperti undang-undang lingkungan AS. Makalah ini membahas dua pertanyaan: (a) apakah perjanjian investasi bilateral Bangladesh, Malaysia, dan AS memiliki ketentuan khusus untuk melindungi lingkungan di negara asal? (b) haruskah perlindungan lingkungan dipertimbangkan selama masuknya investasi asing di negara Bangladesh, Malaysia dan Amerika Serikat? Dengan menggunakan metode penelitian doktrinal, penulis menganalisis secara kritis 40 BIT yang ditandatangani oleh negara Bangladesh, Malaysia dan AS dengan berbagai negara untuk mengeksplorasi apakah ada referensi khusus untuk melindungi lingkungan. Kami menemukan bahwa BIT yang ada terutama memiliki ketentuan untuk mempromosikan dan melindungi investasi asing, dan 7 dari 40 BIT memiliki referensi khusus untuk melindungi lingkungan. Oleh karena itu, pemerintah harus mempertimbangkan faktor penting ini untuk dimasukkan saat menandatangani BIT di masa mendatang.Kata Kunci: Perjanjian investasi bilateral, perlindungan lingkungan, Bangladesh, Malaysia, Amerika Serikat. АннотацияВ отсутствие какого-либо глобального договора Двусторонние Инвестиционные Договоры (ДИД) играют важную роль в регулировании иностранных инвестиций в принимающих странах. По данным Конференции Организации Объединенных Наций по торговле и развитию в настоящее время действует 2361 ДИД, и, как и другие члены Всемирной Торговой Организации, Бангладеш, Малайзия и США также подписали ДИД для облегчения торговли. Основная цель экономической глобализации – это экономическое развитие развивающихся и наименее развитых стран, а также получение выгод для стран базирования. Законы Бангладеш и Малайзии об иностранных инвестициях не содержат конкретных положений о защите окружающей среды и не поддерживают высокие стандарты, такие как законы США об окружающей среде. В настоящей статье рассматриваются два вопроса: (а) есть ли в Двусторонних Инвестиционных Договорах Бангладеш, Малайзии и США какие-либо конкретные положения по защите окружающей среды в принимающей стране? (б) следует ли учитывать защиту окружающей среды при ввозе иностранных инвестиций в Бангладеш, Малайзию и США? Используя метод доктринального исследования, мы критически проанализировали 40 ДИД, подписанных Бангладеш, Малайзией и США с разными странами, чтобы выяснить , есть ли какие-либо конкретные ссылки на защиту окружающей среды. Мы обнаружили, что существующие ДИД в основном содержат положения о поощрении и защите иностранных инвестиций, а 7 из 40 ДИД содержат конкретные ссылки на защиту окружающей среды. Таким образом, правительству следует учитывать этот важный фактор при подписании будущих ДИД.Ключевые слова: Двусторонние инвестиционные договоры, охрана окружающей среды , Бангладеш, Малайзия, Соединенные Штаты Америки